The Effect of Guided Imagery to The Level of Anxiety of Trimester III Pregnant Woman in The Working Area of Mijen Health Center in Semarang City - Wulandari, Priharyanti; Sofitamia, Alifia; Kustriyani, Menik (Universitas Muhammadiyah Semarang, 2019)
Background: Pregnancy is a time when there are dramatic changes both psychologically and biologically that can cause anxiety. From the results of interviews stated 7 of 10Â third trimester pregnant mother said anxious moment before childbirth. Guided imagery is a therapy to overcome anxiety. The purpose of this study to determine the effect of guided imagery on the anxiety level of pregnant women at Trimester III. Method: Quantitative research type of quasi-experimental design pre and post-test without control. Sampling by purposive sampling. The sample size is 30 respondents. The anxiety was measured using the HRSA questionnaire and analyzed using the Match Pair Test Wilcoxon test. Results: The results of analysis of 30 respondents, before given guided imagery therapy most of the respondents experienced moderate anxiety as many as 18 people (60%). After being given guided imagery treatment most respondents had light anxiety 17 people (56.7%). The result of the Wilcoxon test shows p-value 0.000 (p-value <0,05), Ho is rejected and Ha is accepted. Conclusion: There is an influence of guided imagery on the anxiety level of third-trimester pregnant women in the Working Area of Mijen Health Center in Semarang City with a p-value of 0.000 which means that guided imagery can reduce the anxiety level of third-trimester pregnant women.Â